Contribution of Agricultural Cooperatives to Smallholder Potato Farmers’ Livelihood: A Case Study of Mubuga Cooperative in Nyarusizasub-County Kisoro District. - Niringiyimana, Steven (Kabale University., 2024)
This study aimed to assess the contributions of Mubuga agricultural co-operatives to smallholder farmers. The Study's specific objectives were to find out the services offered by Mubuga agricultural cooperative and assess the impact of Mubuga agricultural co-operative on smallholder farmers’ livelihood. A case research study design was designed. A sample size of 99 respondents was selected from Nyarusiza Sub-county, Kisoro district. The results that revealed the majority of respondents were aged between 35 and 65 years old and female respondents dominated in cooperatives. The services offered were: offering loans, provision of agricultural inputs, market creation, construction of storage facilities, provision of seeds, supply of chemicals, and sensitization of farmers. The impact of the Mubuga agricultural cooperative on smallholder farmers included access to agricultural inputs and construction of storage facilities, increased income, and paying school fees for their children. The study concluded that smallholder potato in farmers in Nyarusiza Sub county Kisoro district benefited substantially from Mubuga agricultural cooperative. It was recommended that the government should take some awareness programs about Co-operative Society through social campaign programs starting from the local council using Radio so that people can understand the importance of Cooperative initiatives and accordingly can make practical efforts of joining them in this regard.